Term of Circumstance in issuing laws by decision in the Palestinian constitutional system - Remawi, Abdelmalik Taleb; Saleem, Hasan Jamil (Journal of Economic, Administrative and Legal Sciences, 2022)
The President’s authority and technique of legislating laws during the absence / recess of the legislature is an exceptional and a restricted tool. Perhaps the term of circumstance which is widely defined as the state of necessity is the most important restriction in this context. This issue has been the focus of this study which aimed at clarifying how ostensible versus how ambiguous the state of necessity ought to be. The study also aimed at clarifying the limits of the President’s discretion authority in determining the existence of a state of necessity in addition to whether this is a sole authority for the President and how expansive this authority is and whether it replaces and equalizes the original authority of the legislature. These objectives were achieved by analyzing the relevant provisions of the Palestinian Basic Law and a number of comparative constitutional systems in addition to national and comparative legal jurisprudence. In this work, the concept of the circumstance of necessity and its conditions were defined. The theory of necessity was distinguished from other similar theories and concepts, most notably the theory of exceptional circumstances, which are often confused. However, the problem raised in the study was the extent of clarity of the legal texts regulating the term of the circumstance as a basic determinant of the President’s authority to legislate. In conclusion, it became clear that defining the state of necessity is a basic determinant of whether the President’s authority to legislate is compatible with the legislative organization of the state of necessity. Throughout the research it was revealed that there is a state of legislative omission/ shortcoming in terms of defining the term of circumstance including vagueness of relevant expressions. Consequently, this has unduly opened the doors for unlimited discretion authority of the President in this regard. The study concluded that this ought not be the first option for the executive authority to use. Therefore, it is necessary to determine in a constitutional text the cases in which the term of circumstance of necessity is realized. This would turn the President’s choice of exercising legislative authority into an exception that would be resorted to after calling the Legislative Council to convene in an extraordinary session as a first option.